1993
DOI: 10.1002/star.19930450406
|View full text |Cite
|
Sign up to set email alerts
|

Starch Swelling Power, Grain Hardness and Protein: Relationship to Sensory Properties of Japanese Noodles

Abstract: The starch swelling power tests have been reported to be a promising method for predicting the eating quality of Japanese white salted noodles. The relationships between starch swelling power and noodle eating quality were examined for a range of commercial Australian‐wheat cultivars from two growth seasons. Starch swelling power was found to be dependent on the cultivar, growth site and growth season of the wheat. Analyses of the first season's samples showed highly significant relationships between swelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 7 publications
6
52
0
1
Order By: Relevance
“…These results suggest the Pinb locus affects noodle softness and explains 30% of the variation (SS bulked samples/SS parents = 0.098/0.322) between Sunco and Chuanyu 12 for noodle softness. These results corroborate Konik et al (1993), who found the grain hardness variable improved their model for predicting quality parameters, including noodle softness scores. For noodle 'smoothness' and 'elasticity', noodles made from soft-grained or hard-grained, bulked genotypes had the same scores, statistically (Table 1).…”
Section: Taste Panel Textural Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…These results suggest the Pinb locus affects noodle softness and explains 30% of the variation (SS bulked samples/SS parents = 0.098/0.322) between Sunco and Chuanyu 12 for noodle softness. These results corroborate Konik et al (1993), who found the grain hardness variable improved their model for predicting quality parameters, including noodle softness scores. For noodle 'smoothness' and 'elasticity', noodles made from soft-grained or hard-grained, bulked genotypes had the same scores, statistically (Table 1).…”
Section: Taste Panel Textural Analysissupporting
confidence: 89%
“…The noodle sheet was prepared according to the method described by Konik et al (1993), with some modification. Flour was mixed with water (32% by weight of flour) and NaCl (2% by weight) with a Kenwood (UK) tabletop mixer using a flat mixing paddle.…”
Section: Noodle Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The swelling power and solubility index were determined by the methods of Konik et al [13] and Gudmundsson and Alliasson [14], in a thermostatic Clifton water bath over a temperatures range of 50-95…”
Section: Determination Of Functional Propertiesmentioning
confidence: 99%